1996
DOI: 10.1136/oem.53.10.692
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of exposure to polycyclic aromatic hydrocarbons in engine rooms by measurement of urinary 1-hydroxypyrene.

Abstract: Objective-Machinists have an increased risk of lung cancer and bladder cancer, and this may be caused by exposure to carcinogenic compounds such as asbestos and polycyclic aromatic hydrocarbons (PAHs) in the engine room. The aim of this study was to investigate the exposure of engine room personnel to PAHs, with 1-hydroxypyrene in urine as a biomarker. Methods-Urine samples from engine room personnel (n = 51) on 10 ships arriving in different harbours were collected, as well as urine samples from a similar num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…Moen et al (1996) found traces of degraded hydrocarbon products and other chemicals in the urine of ship engineers 51) . The clinical importance of these findings, however, is still unclear.…”
Section: Occupational Cancermentioning
confidence: 99%
“…Moen et al (1996) found traces of degraded hydrocarbon products and other chemicals in the urine of ship engineers 51) . The clinical importance of these findings, however, is still unclear.…”
Section: Occupational Cancermentioning
confidence: 99%
“…However, this risk remains lower than that of merchant ships seamen and mainly those of oil tankers. It is also shown that the risk of lung cancer is particularly increased among engine room seamen [12]; this is the situation of our third patient who had worked for 21 years in the engine room aboard deep-sea fishing vessels (with 750 horsepower engines powered by diesel). The occupational origin is quite pronounced in this situation because this fisherman has never smoked before.…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, the fisherman, because of his daily work, is well exposed to some chemicals recognised as carcinogenic by International Agency for Research on Cancer with bronchopulmonary tropism; this is the case of the mechanic fisherman in our second case who was exposed to benzene and benzopyrene contained in the exhaust gases emitted during navigation. This exposition is more important during engine maintenance operations and more particularly during assembly/disassembly of the carburettors [12]. Indeed, this fisherman who worked 25 years on board costal fishing vessels (2 longliners and a trawler) says that the engines he worked on (engines from 150 to 200 horsepower all powered by diesel) were often in a precarious state, leakages of diesel exhaust ducts were quite frequent invading the restricted space of the engine room and failures in full navigation were not uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Diesel oil contains PACs (7) and its contribution to HMA paving personal-breathing zone exposures has previously been noted. One study of road pavers in Hungary (Tompa et al (8) ) examined chromosomal aberrations (CAs) in blood samples and found that increases in CAs could be attributed to the presence of genotoxic agents other than those in asphalt emissions, mainly compounds in diesel exhaust and in the petroleum-based solvent used for cleaning the equipment.…”
Section: Introductionmentioning
confidence: 99%